Regulatory T cells in health and disease - Liston, Adrian (Progress in molecular biology and translational science ;, 2015)
Regulatory T Cells in Health and Disease focuses on the mechanism by which T cells become regulatory T cells, the processes which control the number of regulatory T cells in the blood and tissue, and the ways in which regulatory T cell prevent autoimmune disease and interact with infections and cancer. Contains contributions from leading authorities in the field of regulatory T cell biology Informs and updates on all the latest developments in the field Explores the processes which control the number of regulatory T cells in the blood and tissue, and the ways in which regulatory T cell prevent autoimmune disease and interact with infections and cancer.